Organizational Culture and Job Stress Through Contra Productive Behavior of Basic School Teachers - Nuzulurrizqi Arief Wicaksono; Bedjo Sujanto; Matin Matin (EDUTEC : Journal of Education And Technology, 2020)
This study aims to obtain information about the influence of organizational culture and job stress on contra productive behavior of public elementary school teachers in Pulo Gadung sub-district. This research is an Associative quantitative research. The research was conducted using a survey method with the data analysis technique used to answer the hypothesis is the path analysis technique. The population in this study was 688 respondents, and a sample of 253 respondents were selected using random sampling. The research is focused on two aspects that determine contra productive behavior; organizational culture and job stress. The results of the analysis concluded that (1) there is a direct influence of organizational culture on contra productive behavior, (2) there is a direct effect of job stress on contra productive behavior, (3) there is a direct influence of organizational culture on job stress.